Experimental evaluation of human grasps using a sensorized object - Roa, Maximo A.; Koiva, Risto; Castellini, Claudio (Proceedings of the IEEE RAS and EMBS International Conference on Biomedical Robotics and Biomechatronics, 2012)
Grasp quality measures have been studied for long time, given their importance to evaluate the goodness/convenience of a grasp made with a robotic hand. However, the application of these quality measures to grasps made by humans has just recently received some attention. This paper presents an experimental evaluation and comparison of different measures, using data obtained with a sensorized object. The experiment compares power grasps and precision grasps obtained with different number of fingers. The results intend to be a guide to the application of such qualities in the evaluation of robotic grasp actions. © 2012 IEEE.
CRIS-Team Scopus Importer:2021-09-13